2020
DOI: 10.1101/2020.09.23.20200055
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Combinations of PCR and isothermal amplification techniques are suitable for fast and sensitive detection of SARS-CoV-2 viral RNA

Abstract: The newly identified coronavirus, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), causes coronavirus disease 2019 (COVID-19) and has affected over 25 million people worldwide as of 31 August 2020. To aid in the development of diagnostic kits for rapid and sensitive detection of the virus, we evaluated a combination of polymerase chain reaction (PCR) and isothermal nucleic acid amplification techniques. Here, we compared conventional PCR and loop-mediated isothermal amplification (LAMP) methods wi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The RT-PCR test results obtained from nasopharyngeal, oropharyngeal or swap samples from lower respiratory tract such as sputum, tracheal aspirate, or bronchoalveolar lavage are considered variable and potentially unstable (10,12). RT-PCR is the primary method for the diagnosis of COVID-19, but it can cause false negativity (7,13,14). In a study in which Li et al (10) investigated the positivity of the RT-PCR test in patients diagnosed with COVID-19 clinically, they emphasized that there was a high rate of false negativity in the RT-PCR test.…”
Section: Discussionmentioning
confidence: 99%
“…The RT-PCR test results obtained from nasopharyngeal, oropharyngeal or swap samples from lower respiratory tract such as sputum, tracheal aspirate, or bronchoalveolar lavage are considered variable and potentially unstable (10,12). RT-PCR is the primary method for the diagnosis of COVID-19, but it can cause false negativity (7,13,14). In a study in which Li et al (10) investigated the positivity of the RT-PCR test in patients diagnosed with COVID-19 clinically, they emphasized that there was a high rate of false negativity in the RT-PCR test.…”
Section: Discussionmentioning
confidence: 99%
“…171 Several reports proved with the experimental evidence that a LOD as low as two copies can be achieved using a CRISPR-based platform. 32,65 The total testing time using the CRISPR-based platform varies based on the sensor platform utilized for the sensing purposes, ranging from 15 min to ∼1 h. 172−174 The CRISPR-based sensor can be further adapted to detect the infection caused by several The use of nanomaterials can advance the performance of the sensing technologies in virus identification. The integration of nanomaterials into a sensor device, e.g., quartz crystal microbalance, surface acoustic wave (SAW), or chemiresistors, led to many advancements in the field of sensing.…”
Section: Acs Nano Wwwacsnanoorgmentioning
confidence: 99%
“…63,64 Recently, a combination of PCR and isothermal nucleic acid amplification known as loop-mediated isothermal amplification (LAMP) techniques was explored. 65 The idea was to introduce the speed of the LAMP techniques and the accuracy of the PCR method in one single platform. It has been shown that combining LAMP and RT-PCR in one assay to develop RTq(PCR-LAMP) was approximately 100-fold more sensitive than conventional RT-LAMP.…”
Section: Nucleic Acid Amplification Test (Naat)mentioning
confidence: 99%
See 1 more Smart Citation
“…Loop-mediated isothermal amplification (LAMP): In an LAMP experiment, four to six primers are specially designed to identify six to eight regions of the target sequence. 56,57 The amplification begins with an inner primer invasion, then a strand-displacing polymerase elongates the primer and separates the DNA duplex. Subsequently, the first product is displaced by another strand, which is extended by an outer primer.…”
Section: Introductionmentioning
confidence: 99%